Systematic review and recommendations for nonodontogenic toothache. (10th July 2014) - Yatani, H.; Komiyama, O.; Matsuka, Y.; Wajima, K.; Muraoka, W.; Ikawa, M.; Sakamoto, E.; De Laat, A.; Heir, G. M.
Summary Nonodontogenic toothache is a painful condition that occurs in the absence of a clinically evident cause in the teeth or periodontal tissues. The purpose of this review is to improve the accuracy of diagnosis and the quality of dental treatment regarding nonodontogenic toothache. Electronic databases were searched to gather scientific evidence regarding related primary disorders and the management of nonodontogenic toothache. We evaluated the level of available evidence in scientific literature. There are a number of possible causes of nonodontogenic toothache and they should be treated. Nonodontogenic toothache can be categorised into eight groups according to primary disorders as follows: 1) myofascial pain referred to tooth/teeth, 2) neuropathic toothache, 3) idiopathic toothache, 4) neurovascular toothache, 5) sinus pain referred to tooth/teeth, 6) cardiac pain referred to tooth/teeth, 7) psychogenic toothache or toothache of psychosocial origin and 8) toothache caused by various other disorders. We concluded that unnecessary dental treatment should be avoided.